2015
DOI: 10.1186/s40643-015-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of combined UV and chemical mutagenesis treatment of Aspergillus terreus D34 for hyper-production of cellulose-degrading enzymes and enzymatic hydrolysis of mild-alkali pretreated rice straw

Abstract: Background: Microbial production of cellulose-degrading enzymes could be significantly improved using traditional mutagenesis treatment. Development of high-titre cellulase producing mutants drastically reduces the costs involved in cellulase production and downstream processing in commercial-scale enzyme production. Here, we have evaluated the efficacy of different Aspergillus terreus D34 mutants for hyper-production of improved cellulase enzymes utilizing locally available lignocellulosic biomass residues as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…The studied temperature range was limited from 30 to 50 • C. With respect to secondary raw materials, enzymatic hydrolysis using treated strains was more efficient at 37 • C, whereas miscanthus cellulose and wood chips were more efficiently hydrolyzed at 50 • C. The obtained data are consistent with the literature [26,34,[38][39][40][41][42][43][44]. In these studies, the highest enzymatic activity of the relative secondary raw materials was found in the UV strain (92.3 IU/h or 1.5 IU/min).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The studied temperature range was limited from 30 to 50 • C. With respect to secondary raw materials, enzymatic hydrolysis using treated strains was more efficient at 37 • C, whereas miscanthus cellulose and wood chips were more efficiently hydrolyzed at 50 • C. The obtained data are consistent with the literature [26,34,[38][39][40][41][42][43][44]. In these studies, the highest enzymatic activity of the relative secondary raw materials was found in the UV strain (92.3 IU/h or 1.5 IU/min).…”
Section: Discussionsupporting
confidence: 88%
“…The studied microorganisms were consistently subjected to physical and chemical mutagenic effects to enhance their cellulolytic properties. The technique used to induce mutagenesis is described hereafter and was created based on those presented in [20,[26][27][28][29][30] and adapted to the existing conditions.…”
Section: Induced Mutagenesis Of Microorganismsmentioning
confidence: 99%
“…This causes permanent changes in the DNA structure or frame shift mutation which leads to enhanced production of CMCase (Shafique et al, 2011). Our findings are in accordance with Kumar et al (2015) who reported the effect of UV and EMS on cellulases.…”
Section: Strain Improvementsupporting
confidence: 94%
“…Moreover, the combined use of two random mutagenesis methods, like chemical induction and ultraviolet irradiation, have been successfully applied to generate mizoribine producing mutants of Eupenicillium spp. ( Zhang et al, 2010 ) and cellulose-degrading enzymes producing mutants of Aspergillus terreus ( Kumar et al, 2015 ). These results indicate that the combined use of several mutagenesis methods may be a more efficient strategy for improving the fungicide-tolerance of a biocontrol fungus because each technique has a unique mode of action in mutagenesis.…”
Section: Introductionmentioning
confidence: 99%